Management of Acute Atrophic Erythematous Candidiasis in a Diabetes Mellitus Patient: A Case Report - Irene Anastasia Tampubolon; Nurina Febriyanti Ayuningtyas; Aulya Setyo Pratiwi; Gremita Kusuma Dewi; Reiska Kumala Bakti; Ardyta Lintang Maheswari (Interdental Jurnal Kedokteran Gigi (IJKG), 2026)
Introduction: Acute atrophic erythematous candidiasis is an oral mucosal infection caused by overgrowth of Candida spp., commonly associated with immunocompromised conditions such as diabetes mellitus. It presents as painful, erythematous lesions that may impair quality of life if untreated. Case: A 47-year-old male presented with tongue pain. Intraoral examination showed a well-demarcated, elongated erythematous lesion on the anterior one-third of the left dorsal tongue, measuring 2.5 × 1 cm, with a smooth surface and tenderness on palpation. The patient had uncontrolled diabetes mellitus (HbA1c 10.6%) and was on metformin, glimepiride, and amlodipine. Case Management: Fungal culture confirmed Candida glabrata and Candida tropicalis. The patient received topical nystatin oral suspension four times daily for two weeks. After 22 days, complete healing was observed. Poor glycemic control likely increased susceptibility through impaired immunity and changes in the oral environment. The presence of non-albicans Candida species reflects infection patterns in immunocompromised patients. Conclusion: Oral candidiasis is closely associated with diabetes mellitus. Effective management requires antifungal therapy combined with glycemic control and improved oral hygiene.